2021
DOI: 10.1109/access.2021.3096915
|View full text |Cite
|
Sign up to set email alerts
|

Process of Materials Picking Using Augmented Reality

Abstract: The thesis describes the research conducted on the effectiveness of purposed Augmented Reality solutions for material identification in the production system. The research was carried out at the Smart Factory laboratory of the Poznan University of Technology and was divided into two stages. In the first stage, the research has been conducted to identify both of the best variants of application and the AR smart glasses which were used in second stage. The time of identification and completion of production part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Preliminary tests conducted to assist warehouse operators with smart AR glasses confirm the results of studies reported in the literature (e.g., in [ 21 , 25 , 26 , 29 , 30 ]). Workers with little experience get to the designated location faster and make fewer mistakes when handling cargo.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Preliminary tests conducted to assist warehouse operators with smart AR glasses confirm the results of studies reported in the literature (e.g., in [ 21 , 25 , 26 , 29 , 30 ]). Workers with little experience get to the designated location faster and make fewer mistakes when handling cargo.…”
Section: Discussionsupporting
confidence: 78%
“…In logistics, the leading application area for AR is the picking process [ 24 ]. In this process, AR tools typically support the operator in reaching the right location and indicating the quantity to be picked [ 21 , 25 , 26 ]. Research indicates that using augmented reality to communicate order completion information improves time efficiency and picking accuracy (among others [ 27 ]).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…On the other hand, the authors who implemented the Kaizen Teian system obtained the assurance that the personnel assigned to the development of activities in each process is monitored, allowing the standardization of the activities that presented the most failures [18]. Likewise, through the application of this tool, the percentage of damaged boxes was reduced by 27.2%, reducing the waste generated to 18.9% [19].…”
Section: A Process Based On the Standardization Of Product Receptionmentioning
confidence: 99%
“…In particular, motivated by the rise of Industry 4.0, numerous novel technologies were introduced in this field, such as automated guided vehicles (AGV), robots, smart tools, augmented reality (AR) and virtual reality (VR). The recent emergence of virtual technologies – VR and AR – appears to be especially promising for supporting logistics activities but is still quite unexplored (Reif and Walch, 2008; Jovanovikj and Engels, 2020; Zywicki and Bun, 2021). AR can be successfully used for improving logistics workers' efficiency thanks to visual guidance (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, motivated by the rise of Industry 4.0, numerous novel technologies were introduced in this field, such as Automated Guided Vehicles (AGV), robots, smart tools, Augmented Reality (AR), and Virtual Reality (VR). The recent emergence of virtual technologies -VR and ARappears to be especially promising for supporting logistics activities, but is still quite unexplored (Reif & Walch, 2008;Zywicki & Bun, 2021). AR can be successfully used for improving logistics workers' efficiency thanks to visual guidance (e.g., during order picking), while VR can be helpful for managing remote objects in dangerous environments and for training workers (Fang et al, 2019;Matsumoto, 2019;Fang & An, 2021;Yigitbas et al, 2020;Grabowski et al, 2021).…”
Section: Introductionmentioning
confidence: 99%